Review on the Developments of Structure, Construction Automation, and Monitoring of Intelligent Construction - Liu, Kewei; Meng, Qingfei; Kong, Qingzhao; Zhang, Xihong (MDPI AG, 2022)
The building and construction industry is a traditional industry that features high-capacity investment, long return period, high environment impact, and low technology demand in the past decades. With the fast development of technology and the demand for environmental sustainability, it is inevitable for the building and construction industry to embrace the revolution of technology. Intelligent construction is developed in light of advanced technologies including advanced computing technology, 3D design and manufacturing, automation and control, sensing, unmanned aircraft, and autonomous intelligence. It is also closely integrated with using perceived, analytical, decision-making coordination for building construction with perceived intelligent execution technology in the processes. Currently, there is no consensus definition on “intelligent construction” despite its rapid development. This paper reviews existing and current development in intelligent construction focusing on the following three aspects: (a) new structural forms, which are innovative and with potential or are being applied to automated and mass manufacturing/construction; (b) automated and intelligent construction system; and (c) advanced structure sensing and monitoring technology. These three components do not compromise the entire aspects for intelligent construction, but they have no doubt are the core elements for intelligent construction towards future building systems.